A capability-based view of boards: A new conceptual framework for board governance - KLARNER, Patricia (Institutional Knowledge at Singapore Management University, 2021)
A key role of board directors is to govern corporate strategy. Whereas prior research has provided insights into board roles and activities regarding board governance, the underlying capabilities required to govern effectively remain understudied. This article explores and explicates a capability-based view of board actions in which the specific capabilities that enable boards to govern strategic activities are identified. We specifically examine the conceptual foundations and different types of board capabilities, drawing on illustrative cases as well as information from interviews with board directors in the United States, Asia, and Europe. We then discuss several future research directions that can enrich our understanding of the effects of board capabilities on board governance. This article introduces a fine-grained perspective on board governance that examines the individual director, interpersonal, and board levels. By highlighting the need to build the foundation of governance capabilities at multiple levels, we extend our understanding of the compositional challenges for boards and their governance.